Sulfate availability affects ABA levels and germination response to ABA and salt stress in Arabidopsis thaliana - Cao, Minjie; Speiser, Anna; Wirtz, Markus; Hell, Rüdiger (The plant journal, 2013)
Sulfur‐containing compounds play a critical role in the response of plants to abiotic stress factors including drought. The phytohormone abscisic acid (ABA) is the key regulator of responses to drought...
Gesehen am 27.01.2017